2003
DOI: 10.1302/0301-620x.85b1.12781
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic control in Ewing’s sarcoma of the femur treated with chemotherapy, and locally by radiotherapy and/or surgery

Abstract: The role of radiotherapy and/or surgery in the local treatment of Ewing's sarcoma has still to be determined. The outcome of Ewing's sarcoma may differ according to its location and a selection bias towards surgery limits the ability to compare methods of local treatment. We have carried out a retrospective review of 91 consecutive patients treated for non-metastatic Ewing's sarcoma of the femur. They received chemotherapy according to four different protocols. The primary lesion was treated by surgery alone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
2
19
3
1
Order By: Relevance
“…11 In this debate, one must remember that the efficacy of local treatment is not uniform for all patients. The goal of the present study was to identify high-risk patients, who are likely to fail surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11 In this debate, one must remember that the efficacy of local treatment is not uniform for all patients. The goal of the present study was to identify high-risk patients, who are likely to fail surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Current management includes a combination of chemotherapy and excision, with or without radiotherapy. 4,5 Ewing's sarcoma is recognised to be a systemic disease, with between 20% and 30% of patients having detectable metastases at presentation. 6 Cure rates are now around 60% to 70% and are related to the presence of metastases at diagnosis, the size of the tumour and the response to chemotherapy.…”
mentioning
confidence: 99%
“…Most available data, including Cooperative Ewing Sarcoma Study (CESS) 81, 86, and European Intergroup Cooperative Ewing Sarcoma Study (EICESS) 92 trials, on local tumor control in localized Ewing's sarcoma cases suggest superior outcome with local surgical therapy with adequate surgical margins [14][15][16][28][29][30][31] to definitive radiotherapy [16]. Some other studies demonstrated no significant difference in the rates of local recurrence and/or survival between patients who received radiotherapy alone and patients who underwent surgery [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, tumor site (extremity vs. axial) was shown to affect the outcome: patients whose tumors were localized in extremities achieved better results because a high proportion of these patients could be surgically treated either with amputation or with extremity sparing techniques; therefore, adequate surgical margins were possible [14,15,28,31,37]. Naturally, it is difficult to achieve wide resection margins when the axial skeleton is involved, especially with larger lesions.…”
Section: Discussionmentioning
confidence: 99%